Nilai-Nilai yang Terkandung Pada Tradisi Upacara Adat Ulur-Ulur di Telaga Buret - Khofifah, Binti; Rochimayasari, Zulvi; Putranto, Anggoro (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 1 (2024)DO - 10.24843/PJIIB.2024.v24.i01.p05, 2024)
Customs are a tradition or habit that has been carried out by the community repeatedly and continuously and this has been passed down from their ancestors. The ulur-ulur tradition is a tradition carried out by residents of the villages of Sawo, Gedangan, Gamping, and Ngentrong in Campurdarat District. This tradition is carried out as a form of gratitude for God's gift for the abundance of sustenance for the surrounding community in the form of a spring that is said to never run dry. The purpose of this research is to find out why the Ulur-ulur traditional ceremony is important to be preserved and what values can be taken from the preservation of the Ulur-Ulur traditional ceremony. The method used in this research is a qualitative research method with a descriptive approach. The source of data in this study is secondary data obtained through a review of several sources of literature and literature to obtain additional information and as a reference in connecting a theory with the real situation in the phenomenon being studied. The results of the research show that the traditional ceremony of Ulur-ulur is not only beneficial for the preservation of a cultural heritage from the ancestors, but also has more value and function than its implementation. We can see this from the preservation of both local culture and the surrounding environment. and for the values contained in the preservation of the Ulur-ulur traditional ceremony including religious, social, educational, and historical values.